The Effectiveness of Medical Disaster Emergency Kits Compared to Midwife Kits for Midwife Preparedness in Facing Disasters in Disaster-Prone Areas - Maulani, Nurul; Rismayani, Rismayani; Afriannisyah, Entan (Babali Publisher, 2024)
Introduction: Every country needs preparation to face disasters especially for Indonesia which is in the ring of fire, an active volcano cluster. In an emergency to provide first aid, the Midwife can perform health services outside her authority according to her competence. First aid aims to save the client's life or circumstances that threaten the client's life. Medical disaster preparation kits compared to midwife kits for midwife preparedness in dealing with disasters in disaster prone areas in UPT Puskesmas Kandang MasBengkulu City in 2023. Methods: This research method uses a quantitative approach using a pre-experimental research design with paired sample t test. The data collection in this study used a questionnaire. The sample of this study were 30 midwives. Results: Indicate that midwife preparedness in facing disasters using medical disaster preparation kits is categorized as good at 63.3%, has a positive attitude of 56.7% midwives when using the Medical Disaster Preparation Kit, that midwife preparedness in facing disasters midwife kits is categorized as bad at 36.30%, has a negative attitude of 56.70%, midwives when midwife Kit. Statistical test results revealed that the value of midwife preparedness in facing disasters using the medical disaster preparation kit and the attitude when using the Medical Disaster Preparation Kit had p < 0.05. Conclusion: The conclusion of this study is that there are differences in midwife preparedness by using the medical disaster emergency kit and the midwife kit for disaster preparation and handling. There is also a difference in the attitude of use towards the medical disaster emergency kit and midwife kit for midwife preparedness in facing disasters.